2020
DOI: 10.18186/thermal.712452
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation in MHD Flow of Viscoelastic Nanofluids With Homogeneous-Heterogeneous Reaction, Partial Slip and Nonlinear Thermal Radiation

Abstract: We investigate the combined effects of homogeneous and heterogeneous reactions in the boundary layer flow of a viscoelastic nanofluid over a stretching sheet with nonlinear thermal radiation. The incompressible fluid is electrically conducting with an applied a transverse magnetic field. The conservation equations are solved using the spectral quasi-linearization method. This analysis is carried out in order to enhance the system performance, with the source of entropy generation and the impact of Bejan number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In 1959, Casson fluid model was pioneered by Casson [26] for prognosis pigment-oil intermission flow. Furthermore, nanofluid boundary layer fluid flow over disparate geometries was premeditated by numerous researchers in [27][28][29][30][31][32][33][34][35][36]. Fluids behave as a solid, if the yield stress is more than applied shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…In 1959, Casson fluid model was pioneered by Casson [26] for prognosis pigment-oil intermission flow. Furthermore, nanofluid boundary layer fluid flow over disparate geometries was premeditated by numerous researchers in [27][28][29][30][31][32][33][34][35][36]. Fluids behave as a solid, if the yield stress is more than applied shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review shows that the entropy generation in laminar mixed convection in cavities is a subject that remains to be explored. Different studies were studied and reported in the literature [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Various aspect of flow and heat transfer over surfaces of channels have been addressed in recent literature works. For instance, the boundary layer heat transfer of viscoelastic nanofluids [3], non-Newtonian nano-fluids [4], micropolar fluids [5], and radiation effects [6] have been addressed recently.…”
Section: Introductionmentioning
confidence: 99%